The world according to Monsanto : pollution, corruption, and the control of the world's food supply - Robin, Marie-Monique (New Press : Distributed by Perseus Distribution, 2010)
""As this powerful book makes clear, Monsanto's innovations create more problems than they solve-above all by helping to concentrate the food system in ever fewer hands, with baleful consequences for the world's small-scale farmers. It's the kind of reporting we need more of, and one hopes it will be at least a partial antidote to all the slick commercials with smiling peasants." ---Bill McKibben, author of Deep Economy" ""We are what we eat, and what we eat is rapidly being determined by one company, Monsanto. Monsanto's seed and food dictatorship is based on corrupting regulatory processes, corrupting science, and destroying democracy. We needed a book that told us the story in detail, with courage-The World According to Monsanto does just that."-Vandana Shiva, author of Earth Democracy and Stolen Harvest" ""An alarming and uncompromising investigation."---Le Monde" ""Sends chills down the spine....After reading this, we can no longer afford to turn a blind eye."---Le Point" "The result of a remarkable three-year investigation that took award-winning journalist and documentary filmmaker Marie-Monique Robin across four continents (North and South America, Europe, and Asia). The World According to Monsanto tells the little-known yet shocking story of this agribusiness giant-the world's leading producer of GMOs (genetically modified organisms)-and how its new "green" face is no less troubling than its PCB- and Agent Orange-soaked past." "Robin reports that, following its long history of manufacturing hazardous chemicals and lethal herbicides, Monsanto is now marketing itself as a "life sciences" company, seemingly conviced about the virtues of sustainable development. However, Monsanto now controls the majority of the yield of the world's genetically modified corn and soy-ingredients found in more than 95 percent of American households-and its alarming legal and political tactics to maintain this monopoly are the subject of worldwide concern." "Released to great acclaim and controversy in France, throughout Europe, and in Latin America, The World According to Monsanto is sure to change the way we think about food safety and the corporate control of our food supply."--BOOK JACKET.